2007
DOI: 10.1007/s11033-007-9206-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of MDR1 C3435T polymorphism with bipolar disorder in patients treated with valproic acid

Abstract: P-glycoprotein (P-gp), an efflux transporter protein, is an ABC transporter encoded by the multidrug resistance 1 gene (MDR1, ABCB1). The common synonymous C3435T polymorphism in exon 26 is reported to associate with lower P-gp functional expression and drug uptake. Many extended pharmacogenomics, functional, and complex disease association studies focused mainly on this polymorphism. We investigated the association of exon 26 C3435T genetic variants of MDR1 gene with susceptibility to bipolar disorder and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For phenytoin, 3435CC seems to confer a lower C 0 [194] and an increased resistance rate [195]. For valproic acid, the available studies did not find a significant effect on kinetics [196] or the response rate [197]. One single study of lamotrigine in 222 Caucasian epilepsy patients reported that 1236CC and the CGC haplotype conferred a higher C 0 /D [198].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…For phenytoin, 3435CC seems to confer a lower C 0 [194] and an increased resistance rate [195]. For valproic acid, the available studies did not find a significant effect on kinetics [196] or the response rate [197]. One single study of lamotrigine in 222 Caucasian epilepsy patients reported that 1236CC and the CGC haplotype conferred a higher C 0 /D [198].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…While many anticonvulsant medications are MDR1 substrates and has been proposed as a potential mechanism of resistance to therapy, most studies have produced inconclusive results regarding the impact of MDR1 polymorphisms and a recent meta analysis of MDR1 C3435T genotype and resistance to anticonvulsant drugs failed to identify any significant association with resistance and MDR1 genotype [154]. In bipolar patients treated with valproic acid, no difference in serum valproic acid concentration was seen in patients exhibiting the C2335T polymorphism [155]. …”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…The DPC localizes to the sarcolemma, and its disruption is associated with various forms of muscular dystrophy. In brain, DTNB is found on neurons primarily in the cortex and hippocampus and it is expressed in postsynaptic membranes, suggesting a role in synaptic transmission [24]. Gaysina et al [25] found evidence for an association of the DTNBP1 (dystrobrevin-binding protein 1) gene with bipolar disorder, and Talbot et al [26] found a link between DTNBP1 and schizophrenia.…”
Section: Down-regulation Of Genes Associated With Bipolar Disordermentioning
confidence: 99%